Watchband‐Like Supercapacitors with Body Temperature Inducible Shape Memory Ability. Issue 16 (20th June 2016) - Liu, Lingyang; Shen, Baoshou; Jiang, Dan; Guo, Ruisheng; Kong, Lingbin; Yan, Xingbin
Abstract : Smart watches have gained worldwide popularity because they can integrate diverse functions all in one. However, their energy storage devices currently being used are placed in the watches, and this design seriously limited the energy support ability and the future boost space. Herein, for the first time, a strategy to integrate energy storage device with watchband is put forward, which is realized by the preparation of watchband‐like solid‐state supercapacitors using graphene coated on TiNi alloy flake as the negative electrode, ultrathin MnO2 /Ni film as the positive electrode, and different gel electrolytes as the separator. Statical and dynamical bending tests both verify that the as‐fabricated devices have excellent electrochemical performance reliability during bending process. The devices also exhibit the distinctive shape memory ability owing to the use of TiNi shape memory alloy. As a state of the art, such a watchband‐like supercapacitor is connected with an electronic watch to show its potential application. Interestingly, this "watchband" can not only support power to the watch, but also can maintain the shape memory property which can be automatically induced by touching it with the human wrist. In addition, it exhibits excellent biocompatibility. Thus, the smart supercapacitor is qualified for a promising candidate for the next‐generation smart watches. Abstract : A novel flexible solid‐state supercapacitor, to integrate energy storage device with watchband, is fabricated for the first time. It exhibits excellent electrochemical stability during bending and distinctive shape memory ability. As a smart energy‐support watchband, it maintains such shape memory property which can be automatically induced by touching it with the human wrist.